1990
DOI: 10.1111/j.1440-169x.1990.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Lineage and Cell Cycle of Small Micromeres in Embryos of the Sea Urchin, Hemicentrotus pulcherrimus

Abstract: A study was made of 1 st cell cycle of small micromeres, segregated at the 5th cleavage cycle, in the sea urchin embryos of Hemicentrotus pulcherrimus. For identification of small micromeres, the embryos were pulse labeled with 5-bromodeoxyuridine (BrdU) at the 1 st cleavage. Using multiparametric microfluorometry equipped with a scanning stage (Tanaka, 1990), DNA content, extent of BrdU incorporation, protein content and the extent of 3H-thymidine labeling were measured on identical individual cells dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 51 publications
(37 reference statements)
2
48
0
Order By: Relevance
“…Given that the nanos gene has been previously detected in the germ line of animal species and is required for their development, it is thought that small micromere descendants are involved in germ cell development. This possibility was supported by the fact that other factors, which are reported to be expressed in the PGC of other animal species, were accumulated in small micromeres (Ogawa et al, 1999;Juliano et al, 2006) and that small micromeres exhibit a slow cell cycle like PGCs (Tanaka and Dan, 1990). However, it has been reported that functional germ cells can give rise to in adult sea urchins after depletion of the micromeres from the embryo (Ransick et al, 1996).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Given that the nanos gene has been previously detected in the germ line of animal species and is required for their development, it is thought that small micromere descendants are involved in germ cell development. This possibility was supported by the fact that other factors, which are reported to be expressed in the PGC of other animal species, were accumulated in small micromeres (Ogawa et al, 1999;Juliano et al, 2006) and that small micromeres exhibit a slow cell cycle like PGCs (Tanaka and Dan, 1990). However, it has been reported that functional germ cells can give rise to in adult sea urchins after depletion of the micromeres from the embryo (Ransick et al, 1996).…”
Section: Introductionmentioning
confidence: 91%
“…Labeling of small micromere descendants was performed according to the method reported by Tanaka and Dan (1990) with some modifications. Embryos were incubated in FSW containing 0.5 M BrdU just after MO injection for 1 hr.…”
Section: Labeling Of Small Micromeres With Brdumentioning
confidence: 99%
“…5A), just after its formation. Its lineage was traced to the prism/pluteus stage, by which time the SMic descendants go through at least two cell divisions (Tanaka and Dan, 1990;Cameron et al, 1987). As a result, several labeled SMic descendants from a single SMic were found in the nascent coelomic pouches.…”
Section: Left/right Determination Is Not Completed At the Fifth Divisionmentioning
confidence: 99%
“…The developmental origin of the germ line and the specification mechanism of sea urchins have long been controversial. Sea urchin SMics have several PGC-like features, such as early segregation at the fifth division, a transcriptionally quiescent state (Pehrson and Cohen, 1986), a slower cell cycle (Tanaka and Dan, 1990), expression of germ line markers (Juliano et al, 2006), and a contribution to germ cell formation in the adult (Yajima and Wessel, 2011a). Yet, when the precursors of these cells, the Mics, are removed from the embryo, the resultant adults are still gravid and form eggs and sperm in the absence of the Mics (Ransick et al, 1996).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation